Effect Of Blood Transfusıon On Lıver Transplant’s Outcomes And Predıctıve Factors On Transfusıon Requırement (Annals of Medical Research, 2021)
None
Keywords: Liver transplantation, Blood transfusion, Postoperative outcomes